The impact of logistics operations on organizational performance in the oil industry: a case study of eni Ghana exploration and production ltd - Banno-Bosompem Jerry (KNUST, 2024)
A thesis submitted to the department of supply chain and information systems, Kwame Nkrumah university of science and technology, Kumasi, in partial fulfilment of the requirements for the award of a degree of master of science in logistics and supply chain management